2021
DOI: 10.3389/fmed.2020.558696
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Injury Prevention in COVID-19 Patients With Acute Respiratory Distress Syndrome

Abstract: Coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was identified in China in December 2019 and became a pandemic in a short period of time. While most infected people might have mild symptoms, older people and people with chronic illnesses may develop acute respiratory distress syndrome (ARDS). Patients with ARDS with worsening hypoxemia require prone positioning to improve the respiratory mechanics and oxygenation. Intubated patients may stay… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 73 publications
(77 reference statements)
1
37
0
5
Order By: Relevance
“…These pressure-induced injuries are a significant burden to hospitals and severely reduce patient quality of life, with yearly treatment costs ranging from £1.4 -£2.1 billion in the UK to exceeding $26.8 Billion (USD) in the US [2][3][4][5][6][7][8][9]. Looking back at how the COVID-19 pandemic has evolved and progressed globally, epidemiological data suggest an increase in PI prevalence within COVID-19 patients [10][11][12][13][14]. In resource-limited critical care settings, severe respiratory disorders and multi-organ dysfunctions associated with emerging pathogens like Severe acute respiratory syndrome (SARS-CoV), avian influenza A (H5N1), the 2009 influenza A (H1N1) pandemic, Middle East respiratory syndrome coronavirus (MERS-CoV), and avian influenza A (H7N9), increase the concomitant risk factors for PI/PU incidence [10,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pressure-induced injuries are a significant burden to hospitals and severely reduce patient quality of life, with yearly treatment costs ranging from £1.4 -£2.1 billion in the UK to exceeding $26.8 Billion (USD) in the US [2][3][4][5][6][7][8][9]. Looking back at how the COVID-19 pandemic has evolved and progressed globally, epidemiological data suggest an increase in PI prevalence within COVID-19 patients [10][11][12][13][14]. In resource-limited critical care settings, severe respiratory disorders and multi-organ dysfunctions associated with emerging pathogens like Severe acute respiratory syndrome (SARS-CoV), avian influenza A (H5N1), the 2009 influenza A (H1N1) pandemic, Middle East respiratory syndrome coronavirus (MERS-CoV), and avian influenza A (H7N9), increase the concomitant risk factors for PI/PU incidence [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…In resource-limited critical care settings, severe respiratory disorders and multi-organ dysfunctions associated with emerging pathogens like Severe acute respiratory syndrome (SARS-CoV), avian influenza A (H5N1), the 2009 influenza A (H1N1) pandemic, Middle East respiratory syndrome coronavirus (MERS-CoV), and avian influenza A (H7N9), increase the concomitant risk factors for PI/PU incidence [10,15]. The pathophysiological congruity between severe respiratory disorders, etiology, PIs due to prolonged prone positioning and medical device-related PIs is evident [10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…This aligns with the existing research on telenursing for skin cleaning, repositioning, and protecting tissue prominences during social distancing. 18 , 19 Interestingly, participants’ views on the consistent use of the skin cleaning PI handbook and telecare consultation with a professional nurse as a challenge to treat and prevent PI. However, previous research specific to PI exudates from COVID-19 patients, 20 we found that CGs training and formalising continuing education with telenursing can reduce skin cleaning PI at home.…”
Section: Discussionmentioning
confidence: 99%
“…As an emergency response to the COVID-19 outbreak in Melbourne, we have developed an infographic on HAPI prevention in the patients with COVID-19 with an acute respiratory distress syndrome in the prone position and communicated it to the partnering health services (57). The need to improve the skills of acute care clinicians in HAPI management emerges with the influx of COVID-19 aged care residents with PI detected on admission (58).…”
Section: Monash Partners Implementation Of the Proposed Capacity Building Frameworkmentioning
confidence: 99%